Long‐term quality of life after esophagectomy with gastric pull‐up. Issue 5 (6th February 2018) - Mantoan, Silvia; Cavallin, Francesco; Pinto, Eleonora; Saadeh, Luca M.; Alfieri, Rita; Cagol, Matteo; Bellissimo, Maria C.; Castoro, Carlo; Scarpa, Marco
Abstract : Background and Objectives: Data on long‐term health‐related quality of life (HRQL) after esophagectomy for cancer show contradictory results. The aim was to analyze long‐term HRQL at 3 or more years after esophagectomy. Methods: Survivors were identified among patients who had undergone esophagectomy during 2007‐2013 using the local clinic database. Quality of life was assessed using the European Organization for Research and Treatment of Cancer QLQ‐C30 and OG25 questionnaires. Specific aspects were selected a priori and compared with published scores from European healthy subjects (mean difference, MD). Results: Sixty‐five long‐term survivors (median follow‐up 4 years) were identified. All functional scales and most symptom scales were clinically similar between EC long‐term survivors and European healthy subjects. Survivors reported more problems concerning eating (MD 13.1, 95% C.I. 10.6‐15.6) and reflux (MD 19.7, 95% C.I. 15.9‐23.5). HQRL variation from discharge to long term was available in 27 participants who reported improvements in role functioning (MD 40.1, 95%C.I. 24.3‐56.0) and dysphagia (MD −41.9, 95% C.I. −51.7 to 32.0). Conclusions: Long‐term HRQL after esophagectomy is similar between EC survivors and European healthy subjects, despite persisting reflux and eating problems. Further research may focus on improvements of postoperative alimentary habits.